Experience of Manual Compression Hemostasis Under Endoscopic Observation for Acute Hemorrhagic Rectal Ulcer - Kawabata, Hideaki (Gastroenterology Res, 2019)
We experienced two cases in which manual compression hemostasis under endoscopic observation was used in patients with acute hemorrhagic rectal ulcer (AHRU). The patients experienced an episode of massive fresh hematochezia, requiring the blood transfusion. Emergent sigmoidoscopy revealed multiple ulcers with a large protuberant visible vessel or with gush-out hemorrhage on the lower rectum. Endoscopic hemostasis by hemoclips and hypertonic saline-epinephrine injection was attempted; however, mechanical mucosal injury induced by hemoclips and needles caused another gush-out hemorrhage. Thus, the site of bleeding was manually compressed by a forefinger under endoscopic observation. After 5 min, compression hemostasis was achieved, and the postoperative course was uneventful. Manual compression hemostasis under endoscopic observation is useful and worth attempting for AHRU.